Periodontal Pathogen Colonization in Young Children by PCR Quantification - A Longitudinal Survey - Takahashi, Karine; Cunha, Robson Frederico [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (Journal Pedodontics Inc, 2018)
Introduction: Periodontal diseases are among the leading causes of premature tooth loss in adults, but the microbiota associated with this problem is established over time in childhood. Aim: This longitudinal study aimed to verify the occurrence of periodontal pathogens in the oral cavity of children aged six, twelve, eighteen and twenty-four months through PCR quantification, correlating them with the oral microbiota of their mothers. Study design: Saliva and oral biofilm samples were collected from mothers and children by using sterilized paper points. Furthermore, a questionnaire was applied in all periods to evaluate hygiene and dietary habits. Results: A positive correlation was found between mother-child pairs in all periods. No correlation was observed between hygiene and dietary habits and occurrence of periodontal pathogens. Conclusion: Early inclusion of children in preventive and biofilm control programs could contribute to preventing acquisition of aggressive pathogens.
Keywords: Saliva; Anaerobic Bacteria; Periodontal Diseases